Sholawat Nariyah Assembly in Building Social Trust: A Perspective on Frazier Moore's Approach to Educational Institutions - Sanafiri, Ahmad Nadif; Hasanah, Rizkiyah (AFKARINA: Jurnal Pendidikan Agama Islam, 2023)
This research aims to evaluate the impact of the Sholawat Nariyah Assembly on community perceptions of Nurul Fatta Islamic Boarding School and understand how these activities affect the image of the institution. The research method used is qualitative with a case study approach. The research subjects included activity participants, community leaders, and internal parties of the boarding school. Data collection techniques included in-depth interviews, direct observation, and analysis of activity documents. Data were analyzed using thematic analysis techniques to identify patterns and main themes related to changes in perceptions and the impact of activities. The results showed that the implementation of the Sholawat Nariyah Assembly on a regular basis has resulted in a significant improvement in the institution's image and community trust, with active participation and support from community leaders who play an important role in improving the community's view of the Nurul Fatta Islamic Boarding School. The research revealed that the activity is effective in strengthening the relationship between the institution and the community through increased transparency, public engagement, and consistent communication.